Localization For Underwater Robot Using Camera And Light Source - Ng, Ping Jian (Universiti Sains Malaysia, 2018)
As of today, ocean is one of the major sources of food, oil and gas. There are so many wonders yet to be discovered under the ocean and it was no easy task as human cannot breathe underwater. Thus, it is better to let robots to do the job. Since they can survive without oxygen and can withstand a great amount of pressure before disfunction. The term we come with robot under water is autonomous underwater vehicle (AUV). However, while AUV does not require oxygen and can withstand great pressure which human cannot, they lack the ability and advantages as well. For example, AUV lacks the precision control as well as sense of direction. A robot does not know where it should go unless you tell it to. We can use Global Positioning System (GPS) to locate a robot on land so that it has “sense of direction”, but GPS does not work well underwater. Advance AUV employs features such as sonar and radar for underwater localization. However, those modules are very expensive. A replacement of sonar and radar would be using camera and floating markers. Camera facing the surface of the water can take image of floating markers, where the position of the markers is already identified. Then, the image can be sent to microprocessor to process the image and position of the AUV can be pinpoint its own location, given the known location of floating markers, through a technique called trilateration. Trilateration is a technique used to determine the coordinate of an unknown point, given 3 distances from 3 points with known coordinate. The result shown the technique was successful.